Involvement Of Sustainability Issues In Value Management: Requisite Factors - Abidin, Nazirah Zainul; Said, Ilias (2006)
For construction to play its part in making society more sustainable, the project practitioners and the decision makers must confront with social, economic and environmental issues throughout the project life.